Evaluation of Sagala Noi Chooranam - A Review of its Therapeutic Potential (International Journal of Ayurveda and Pharma Research, 2025)
The uniqueness of Siddha medicine lies in its holistic approach- the physical, mental, social and emotional well-being are fostered by adopting appropriate lifestyle practices, dietary regimens, safe and effective drugs sourced from the surroundings and therapies specific to this system. The medicine called Sagala noi chooranam is one among the Siddha medicines mentioned in the book Brahmamuni karukkidai soothiram 390. The drug review of the medicine explains about morphology, family, chemical constituents and pharmacological actions of each ingredient. The main sources of review as Siddha text and resources from the database and relevant journals. The main aim of the study is to evaluate the chemical characters and action of the drug Sagala noi chooranam. The secondary aim is to spread awareness about the drug. The conclusion suggests that Sagala noi chooranam may possess therapeutic benefits, but further research is needed to establish its efficacy and safety.